Effect of Chitosan as a Coagulant Aid Combined With Poly Aluminum Chloride Removing of Turbidity From Drinking Water - Abdolmotaleb Seid Mohammadi; Azam Mobarakian; Fatemeh Taherkhani; Ghorban Asgari (Hamadan University of Medical Sciences, 2014)
Chitosan, a biodegradable polymer, is used as an eco-friendly coagulant in a wide variety of applications in water and wastewater treatment. The present study aimed to investigate the effect of chitosan as a coagulant aid combined with poly aluminum chloride (PAC) to enhance coagulating efficiency for bentonite suspensions. A conventional jar test apparatus was used for the tests. The effect of various operational parameters, such as initial pH of the solution (5-9.5), dosage of chitosan (0.5-3.5 mg/L), dosage of PAC (5-35 mg/L) and initial turbidity (50-200 NTU) were investigated. The maximum turbidity removal rates were obtained as pH 8.5 for PAC and pH 7.5 for combined PAC and chitosan (CPC). The coagulating efficiency of bentonite using PAC and CPA was found to decrease with an increase in the pH value of the solutions. The maximum turbidity removal rate was achieved in coagulating by PAC (30 mg/L) alone, and PAC (20 mg/L) combined with chitosan (2.5 mg/L) as coagulant aid with the removal rate of 87% and 96%, respectively. The optimum dosage of chitosan required to obtain the highest removal rate was 2.5 mg/L. Hence, using chitosan as a coagulant aid can not only reduce the required amount of coagulant (35%) but can also enhance the removal turbidity efficiency.